Simulating demand for electrical vehicles using revealed preference data - Áine Driscoll; Seán Lyons; Franco Mariuzzo; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2012)
We have modelled the market for new cars in Ireland with the aim of quantifying the values placed on a range of observable car characteristics. Mid-sized petrol cars with a manual transmission sell best. Price and perhaps fuel cost are negatively associated with sales, and acceleration and perhaps range are positively associated. Hybrid cars are popular. The values of car characteristics are then used to simulate the likely market shares of three new electrical vehicles. Electrical vehicles tend to be more expensive even after tax breaks and subsidies are applied, but we assume their market shares would benefit from an "environmental" premium similar to those of hybrid cars. The "environmental" premium and the level of subsidies would need to be raised to incredible levels to reach the government target of 10% market penetration of all-electric vehicles.
Keywords: 330